Hubungan Dukungan Keluarga Dengan Interdialytic Weight Gain Pasien GGK Yang Menjalani Hemodialisis - Ani Susilowati (STIKES Widyagama Husada, 2026)
Abstract Chronic kidney disease (CKD) is one of the global health problems with an increasing incidence each year. In its advanced stage, patients require renal replacement therapy, one of which is hemodialysis. A common problem among patients undergoing hemodialysis is weight gain between two dialysis sessions, known as Interdialytic Weight Gain (IDWG). IDWG is an important indicator for assessing patient adherence to fluid restrictions, as excessive IDWG can lead to shortness of breath, edema, and even death.Family support plays an important role in helping patients undergo optimal treatment. This study aimed to determine the relationship between family support and IDWG among patients with chronic kidney disease undergoing hemodialysis in the Cut Nyak Dien Room at Dr. Saiful Anwar Hospital, East Java Province.This study employed a descriptive correlational design with a cross-sectional approach. The number of respondents was 60, selected using the purposive sampling technique. Data were collected using a family support questionnaire and an observation sheet, and then analyzed using the Spearman Rank test.The results showed no significant relationship between family support and IDWG (p = 0.536; p > 0.05), with a correlation coefficient of 0.081, indicating a very weak positive relationship. This suggests that the presence of family support does not necessarily reduce IDWG, which may be influenced by other factors such as adherence to fluid restriction, thirst control, sodium intake, duration of hemodialysis, and patient knowledge.Although the statistical analysis showed no significant relationship, family support still plays an important role in enhancing motivation, treatment adherence, and improving the quality of life of patients. Abstrak Gagal ginjal kronis merupakan salah satu masalah kesehatan global dengan angka kejadian yang terus meningkat setiap tahunnya. Pada tahap lanjut diperlukan terapi pengganti ginjal,salah satunya adalah hemodialisis. Masalah utama yang umumnya terjadi pada pasien yang menjalani terapi hemodialisis adalah kenaikan berat badan di antara dua waktu hemodialisis atau disebut Interdialityc Weight Gain (IDWG). Kenaikan IDWG merupakan salah satu indikator penting dalam evaluasi kepatuhan pasien terhadap pembatasan cairan. IDWG berlebih dapat menimbulkan sesak,bengkak bahkan kematian. Dukungan keluarga berperan dalam membantu pasien menjalani pengobatan secara optimal. Penelitian ini bertujuan untuk mengetahui hubungan antara dukungan keluarga dengan kenaikan IDWG pada pasien gagal ginjal kronik yang menjalani hemodialisis di Ruang Cut Nyak Dien RSUD Dr. Saiful Anwar Provinsi Jawa Timur. Jenis penelitian ini adalah deskriptif korelasional dengan pendekatan cross-sectional. Jumlah responden sebanyak 60 orang. Pengumpulan data menggunakan kuesioner dukungan keluarga dan lembar observasi IDWG, kemudian dianalisis menggunakan uji statistik Spearman Rank. Hasil penelitian menunjukkan tidak terdapat hubungan yang signifikan antara dukungan keluarga dengan kenaikan IDWG. Data analisis di peroleh nilai p 0,536 (p>0.05) dan nilai koefisiensi kolerasi sebesar 0,081 yang berarti hubungan dukungan keluarga dengan IDWG bersifat positif sangat lemah. Hal ini menunjukkan bahwa adanya dukungan keluarga belum tentu menurunkan IDWG kemungkinan di sebabkan oleh faktor lain seperti kepatuhan diit cairan, kontrol rasa haus, asupan natrium,lama menjalani hemodialisis dan tingkat pengetahuan pasien.